Gender and mental health service use in bipolar disorder: national cohort study. Issue 6 (November 2020) - Cunningham, Ruth; Crowe, Marie; Stanley, James; Haitana, Tracy; Pitama, Suzanne; Porter, Richard; Baxter, Jo; Huria, Tania; Mulder, Roger; Clark, Mau Te Rangimarie; Lacey, Cameron
Abstract : Background: Despite evidence of gender differences in bipolar disorder characteristics and comorbidity, there is little research on the differences in treatment and service use between men and women with bipolar disorder. Aims: To use routine data to describe specialist mental health service contact for bipolar disorder, including in-patient, community and support service contacts; to compare clinical characteristics and mental health service use between men and women in contact with secondary services for bipolar disorder. Method: Cross-sectional analysis of mental health patients with bipolar disorder in New Zealand, based on complete national routine health data. Results: A total of 3639 individuals were in contact with specialist mental health services with a current diagnosis of bipolar disorder in 2015. Of these 58% were women and 46% were aged 45 and over. The 1-year prevalence rate of bipolar disorder leading to contact with specialist mental health services was 1.56 (95% CI 1.50–1.63) per 100 000 women and 1.20 (95% CI 1.14–1.26) per 100 000 men. Rates of bipolar disorder leading to service contact were 30% higher in women than men (rate ratio 1.30, 95% CI 1.22–1.39). The majority (68%) had a diagnosis of bipolar I disorder. Women were more likely to receive only out-patient treatment and have comorbid anxiety whereas more men had substance use disorder, were convicted for crimes when unwell, received compulsory treatment orders and received in-patient treatment. Conclusions: Although the prevalence of bipolar disorder is equal between men and women in the population, women were more likely to have contact with specialist services for bipolar disorder but had a lower intensity of service interaction.